Unknown Pages of the History of Soviet Art Criticism: Documents from the Personal Archive of M. K. Karger at the Institute for the History of Material Culture of the Russian Academy of Science - Mikhailov, Kirill A.; Grigor’eva, Olga V.; Medvedeva, Maria V. (Actual Problems of Theory and History of Art, 2023)
The article presents a preliminary analysis of the documents of the personal fund of M. K. Karger (F. 85), kept in the scientific archive of the IHMC RAS. Mikhail Konstantinovich Karger was one of the key figures of the Leningrad art school of the 20th century. With his participation, outstanding monuments of ancient Russian stone architecture were discovered and investigated, and the Leningrad school of architectural archeology was established. The study of Karger’s life path has always been complicated by the lack of his detailed official biography. During his lifetime, the scientist was extremely brief and cautious in official documents and did not leave diaries or letters. The researcher’s personal fund contains important information, both of a biographical nature and on scientific activities within the framework of the school of Old Russian architectural archaeology and Soviet art criticism. In addition, some rare biographical documents of M. K. Karger have been found in the archives of Kazan, Samara, and St. Petersburg. An appeal to a previously unknown set of documents can provide a fresh look at the monumental figure of a multifaceted scientist who combined skills as a talented archaeologist, architectural historian, and expert in Old Russian art. The study was conducted within the framework of the implementation of the program of the Federal Research Institute of the Russian Academy of Sciences on the topic of state work No. FMZF–2022–0015.